2021
DOI: 10.1016/j.yebeh.2021.107923
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of seizures, status epilepticus, and EEG findings in critically ill patient with COVID-19

Abstract: Objective Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has a myriad of neurological manifestations and its effects on the nervous system are increasingly recognized. Seizures and status epilepticus (SE) are reported in the novel coronavirus disease (COVID-19), both new onset and worsening of existing epilepsy, however the exact prevalence is still unknown. The primary aim of this study was to correlate the presence of seizures, status epilepticus, and specific critical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…In the current study, we observed that seizures (as a presenting manifestation) in patients with COVID-19 are either acute symptomatic seizures (62.5%) or exacerbation of a pre-existing epilepsy/functional seizures (34.4%); only rarely a seizure heralds the beginning of an epileptic process (3.1%). Furthermore, a recent study showed that while seizures and status epilepticus could be encountered in patients with COVID-19, their occurrence did not correlate with the patients' functional outcome [13]. Our observation is consistent with that in previous studies [4,14] and it has important clinical implications.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we observed that seizures (as a presenting manifestation) in patients with COVID-19 are either acute symptomatic seizures (62.5%) or exacerbation of a pre-existing epilepsy/functional seizures (34.4%); only rarely a seizure heralds the beginning of an epileptic process (3.1%). Furthermore, a recent study showed that while seizures and status epilepticus could be encountered in patients with COVID-19, their occurrence did not correlate with the patients' functional outcome [13]. Our observation is consistent with that in previous studies [4,14] and it has important clinical implications.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are also consistent with other New York based studies including one from Columbia University where 14% had GPDs with a similar number (8%) having electrographic seizures on continuous recordings ( Waters et al, 2021 ), as well as from a large cohort of 192 patients at Northwell using a mixture of continuous and routine recordings where the overall presence of epileptiform discharges was 39.6% with a prevalence of GPD’s of 19.3% and seizures of 4.1%. Our results also mirror those in other parts of the United States including a study in Michigan which reported high rates of generalized periodic discharges with triphasic morphology (21%), GRDA (18%) and non-triphasic GPDs (9%) and a comparable incidence of electrographic seizures (11%) on routine and continuous recordings ( Danoun et al, 2021 ) as well as a study from the Cleveland Clinic ( Louis et al, 2020 ), which reported GPDs and seizures in 32% and 9% of patients who underwent primarily continuous as well as routine EEG. In all of these studies, the most common reason for EEG monitoring was severely abnormal mental status followed by paroxysmal motor events concerning for seizures, and the proportion of patients on antiseizure medications was high (27-55%).…”
Section: Discussionsupporting
confidence: 88%
“…Epilepsy patients constituted a small proportion in both groups, and the majority of them had cerebral involvement. Increased seizure frequency and new-onset seizures during COVID-19 have been reported previously, and our data were similar to these [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%